PROFESSIONAL WRITING ANXIETY AMONG INDONESIAN EFL STUDENTS: TYPES, CAUSES, AND COPING STRATEGIES - Jusak Patty (LPPM Universitas PGRI Jombang, 2025)
This study investigated professional writing anxiety among English Education students at Pattimura University, examining anxiety levels, types, causes, and coping strategies in workplace communication contexts. Using a sequential explanatory mixed-methods design, 57 students completed adapted Professional Writing Anxiety Inventory and Professional Writing Anxiety Causes Inventory instruments, while 12 purposively selected participants engaged in semi-structured interviews. Results revealed moderate anxiety levels across the population (M = 3.17), with cognitive anxiety emerging as the dominant dimension (M = 3.47), followed by somatic anxiety (M = 3.32) and avoidance behavior (M = 2.73). Time pressure served as the primary trigger for somatic responses, with 66.6% of students experiencing heart palpitations during time-constrained professional writing tasks. Causal analysis identified insufficient practice in professional writing formats (M = 3.67), linguistic difficulties (M = 3.63), and time pressure concerns (M = 3.60) as primary contributing factors. Qualitative findings revealed four sophisticated coping strategies: systematic preparation and quality control, cognitive and environmental regulation, social support utilization, and emerging technology integration. The study demonstrates that professional writing contexts create distinct anxiety patterns compared to general academic writing, requiring specialized pedagogical approaches. These findings contribute theoretical understanding of context-specific anxiety manifestation while providing evidence-based guidance for Professional Writing curriculum development in Indonesian EFL contexts.